SIFAT-SIFAT LANJUT NEUTROSOFIK MODUL - ., Suryoto; Irawanto, Bambang; Puspita, Nikken Prima (MATEMATIKA, 2016)
Neutrosophic module over the ring with unity is an algebraic structure formed by a neutrosophic abelian group by providing actions scalar multiplication on the structure. The elementary properties of neutrosophic module have been looked at, that are intersection dan summand among neutrosophic submodules are neutrosophic submodule again, but it not true for union of neutrosophic submodules. In this article discussed the advanced properties of the neutrosophic module and the algebraic aspects respect to this structure, including neutrosophic quotient module and neutrosophic homomorphism module and can be shown that most of the properties of the classical module still true to the neutrosophic structure, especially with regard to the properties of neutrosophic homomorphism module and the fundamental theorem of neutrosophic homomorphism module.